Ісак Прохорович Мазепа (1884 – 1952) - Половець, В. (Сiверянський лiтопис, 2017)
Стаття присвячена Ісаку Прохоровичу Мазепі – українському політичному і громадському діячеві, голові уряду Директорії та одночасно міністру внутрішніх справ
цього уряду. Завдяки своїм здібностям він з міщанської сім’ї козацького походження
зміг закінчити семінарію і Санкт-Петербурзький університет, а в часи Української
Центральної Ради і Директорії активно працювати на революцію. Статья посвящается Исаку Прохоровичу Мазепе – украинскому политическому и
общественному деятелю, председателю правительства Директории и одновременно
министру внутренних дел этого правительства. Благодаря своим способностям, он
из мещанской семьи казацкого происхождения смог окончить семинарию и Санкт-Петербургский университет, а во время Украинской Центральной Рады и Директории активно работать на революцию. Issac Prokhorovych Mazepa was born on 16 August 1884 in the village of Kostodobriv,
Novhorod-Siverskyi Uyezd (District), Chernihiv Governate (Region). The family was large
and had many children. This petty bourgeois family was of Cossacks descent. The father
worked hard in his wealthy household. Isaac’s elder brother Karpo helped the father. Younger
brother Kalenik immigrated to America before the break of the World War I. No information
is available on the lives of Issac’s younger brothers and his sister. Upon graduation from the
bursa, Isaac studied at Chernihiv seminary. In 1904, he became a student of Saint-Petersburg
University. Although he studied at the natural sciences faculty, he also was interested in
philosophy, history, and economic sciences. During his study at the university, Isaac became
an activist of the Ukrainian Social Democratic Party that involved him in revolutionary
events of 1917-1921.
Issac Mazepa was the Internal Minister in the Directoria government. In 1919, by the
order of the Directoria, he was appointed the Prime Minister while at the same time keeping
the position of the Internal Minister. Under the Bolsheviks’ pressure, however, the Directoria
actually fell. I.Mazepa stayed in the office of the Prime-Minister till 28 May 1920. After
resignation, he left for abroad. He worked as a lecturer at the Ukrainian Free University in
Prague, and as a professor at the Technical Economic Institute in Bavaria. I.Mazepa died on
18 March 1952 and was buried in Augsburg, Germany.
His legacy of licentiate agronomist includes also a collection of interesting historical and
political works on national liberation struggle of the Ukrainian people during the period of
Central Rada and Hetmanate.